3D relative dose measurement with a μm thin dosimetric layer. (March 2021) - Schuster, Christiane; Kuntz, Florent; Strasser, Alain; Härtling, Thomas; Dornich, Kay; Richter, Daniel
Abstract: A μm thin dosimetric coating material based on inorganic phosphor particles NaYF4 :Yb 3+, Er 3+ has been developed. A dose dependency of the luminescence decay time is observed in the μs - ms domain which allows relative dose measurement in the kGy range. Dose values are obtained from decay time evaluation which facilitates a measurement independent of luminescence emission intensity. Here, near-IR luminescence after excitation with 5 ms pulses of near-infrared light is analyzed. The dosimetric material can be directly sprayed onto the surface of objects and therefore renders particularly useful for dose distribution measurements on non-planar geometries. Because of the μm thickness and the direct contact of the dosimetric material to the entire surface of an object, the results can be considered as 'true' surface doses. Three dimensional dose maps were derived by scanning the entire surfaces of irradiated objects. Proof-of-concept is provided by good agreement in dose results as well as dose pattern with film dosimetry (Risø B3 strips) and the approach therefore qualifies especially for use in 3D dose mapping of complex geometries. This novel approach provides unprecedented insights into dose distributions of irradiated objects of complex geometries, as exemplified by dose results for outer and inner surfaces of e-beam irradiated bottles for two different irradiation set-ups. Highlights: Dose dependency of luminescence decay time. True surface dose because dosimetric material adheres directly to object's surface. 3-dimensional surface mapping of dose distributions in unprecedented detail.